2008
DOI: 10.1210/en.2008-0263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Des-acyl Ghrelin on Adiposity and Glucose Metabolism

Abstract: Ghrelin, a gastric peptide hormone, has been reported to regulate GH secretion and energy homeostasis. Here, we examined the effect of des-acyl ghrelin driven from the fatty acid-binding protein-4 (FABP4) promoter on adiposity and glucose metabolism. A high level of expression of des-acyl ghrelin (692 +/- 293 fmol/g fat) in adipose tissue was detected in FABP4-ghrelin transgenic mice, but not in wild-type littermates. Circulating des-acyl ghrelin was significantly higher in FABP4-ghrelin transgenic mice (8409 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
94
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 31 publications
12
94
0
8
Order By: Relevance
“…A regulatory role of UAG on adipogenesis has been reported in animal studies (3,23). Zhang et al (23) reported a reduction in white adipose tissue and resistance to high-fat diet-induced obesity with an increase in plasma UAG concentrations in transgenic fatty acid-binding protein 4 mice.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A regulatory role of UAG on adipogenesis has been reported in animal studies (3,23). Zhang et al (23) reported a reduction in white adipose tissue and resistance to high-fat diet-induced obesity with an increase in plasma UAG concentrations in transgenic fatty acid-binding protein 4 mice.…”
Section: Discussionmentioning
confidence: 92%
“…Zhang et al (23) reported a reduction in white adipose tissue and resistance to high-fat diet-induced obesity with an increase in plasma UAG concentrations in transgenic fatty acid-binding protein 4 mice. In contrast, Thompson et al (3) observed parallel adipogenic effects of UAG with AG, via a mechanism independent of the GHS-R 1a in rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct metabolic effects of DAG cannot be excluded in view of the reported GHS-R1a-independent (AG-independent) effects of DAG, which include improved glycemic control through the modulation of glucose and medium-chain fatty acid uptake (2,6,35,36). Another indication of the importance of DAG levels as a potential physiological inhibitor of AG action has been reported already by the above-mentioned studies of transgenic mice overexpressing DAG (32,33,37), which were lighter and shorter compared with controls. In another example of its antagonistic effects, DAG was found to suppress AG-induced neuronal activity in the arcuate nucleus of rats, thus suppressing the induction of food intake by AG (21).…”
Section: European Journal Of Endocrinologymentioning
confidence: 98%
“…Glucose tolerance tests showed glucose levels to be significantly lower in Fabp4-ghrelin transgenic mice than in the controls after glucose administration. Insulin sensitivity testing showed that Fabp4-ghrelin transgenic mice exhibited a significant greater hypoglycemic response to insulin (33). The inhibition of AG action by GHS-R1a blockade might, however, have unwanted side effects.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…In 3T3-L1 cell lines, over-expression of ghrelin significantly inhibits differentiation of adipocytes (Zhang et al, 2004) and markedly decreases mRNA and protein levels of PPAR , a marker of adipocyte differentiation. Over-expression of ghrelin in adipose tissue under the control of FABP4 promoter (Zhang et al, 2008) significant decreases the amount of adipose tissue and renders the mice resistant to diet induced obesity, which indicate that ghrelin may impair the development of adipose tissue (Zhang et al, 2008).…”
Section: Ghrelin and Cell Differentiationmentioning
confidence: 99%